An intronic mutation c.6430-3C>G in the F8 gene causes splicing efficiency and premature termination in hemophilia A. Issue 4 (June 2018) - Xia, Zunjing; Lin, Jie; Lu, Lingping; Kim, Chol; Yu, Ping; Qi, Ming
Abstract : N/A: Hemophilia A is a bleeding disorder caused by coagulation factor VIII protein deficiency or dysfunction, which is classified into severe, moderate, and mild according to factor clotting activity. An overwhelming majority of missense and nonsense mutations occur in exons of F8 gene, whereas mutations in introns can also be pathogenic. This study aimed to investigate the effect of an intronic mutation, c.6430-3C>G (IVS22-3C>G), on pre-mRNA splicing of the F8 gene. We applied DNA and cDNA sequencing in a Chinese boy with hemophilia A to search if any pathogenic mutation in the F8 gene. Functional analysis was performed to investigate the effect of an intronic mutation at the transcriptional level. Human Splicing Finder and PyMol were also used to predict its effect. We found the mutation c.6430-3C>G (IVS22-3C>G) in the F8 gene in the affected boy, with his mother being a carrier. cDNA from the mother and pSPL3 splicing assay showed that the mutation IVS22-3C>G results in a two-nucleotide AG inclusion at the 3′ end of intron 22 and leads to a truncated coagulation factor VIII protein, with partial loss of the C1 domain and complete loss of the C2 domain. The in-silico tool predicted that the mutation induces altered pre-mRNA splicing by using a cryptic acceptor site in intron 22. The IVS22-3C>G mutation was confirmed to affect pre-mRNA splicing and produce a truncated protein, which reduces the stability of binding between the F8 protein and von Willebrand factor carrier protein due to the loss of an interaction domain.